Antibacterial Evaluation of Some Schiff Bases Derived from 2-Acetylpyridine and Their Metal Complexes - Gwaram, N.S.; Ali, H.M.; Khaledi, H.; Abdulla, M.A.; Hadi, A.H.A.; Thong, Kwai Lin; Ching, C.L.; Ooi, C.L. (2012)
A series of Schiff bases derived from 2-acetylpyridne and their metal complexes were characterized by elemental analysis, NMR, FT-IR and UV-Vis spectral studies. The complexes were screened for anti-bacterial activity against Methicillin-resistant Staphylococcus aureus (MRSA), Acinetobacter baumanni (AC), Klebsiella pneumonie (KB) and Pseudomonas aeruginosa (PA) using the disc diffusion and micro broth dilution assays. Based on the overall results, the complexes showed the highest activities against MRSA while a weak antibacterial activity was observed against A. baumanii and P. aeruginosa.